Climate and yield variability of major cereal crops in Marsyangdi River Basin, Nepal - Ganesh R. Joshi; Binaya Joshi; Kshitiz R. Joshi (Academia Environmental Sciences and Sustainability, 2025)
Climate change has impacted Nepal’s agricultural sector in various ways. This has resulted a change in the patterns of rainfall and temperature, and an increase in the occurrence of extreme weather events. Due to this, the growth and productivity of many crops has been challenged. In this context, this study uses time series data to assess the impacts of climatic variables on crop yield. The analysis was carried out in 4 districts of the Marsyangdi River Basin. A Mann–Kendall test and a Sen’s slope test were used to analyze the annual and seasonal temperature and rainfall variation, while a compound annual growth analysis was performed for the yield variation of different crops. Multivariable linear regression was used to analyze the effects of climatic variables on the yield of crops. The results revealed that there was an increasing trend in temperature and the yield of crops, with a decreasing trend in rainfall. The growth of maximum temperature during the winter crops’ growing season was the highest while there was variation in the case of the summer season (April/May–Sept/Oct). There was wide variation in the yield of cereal crops in the districts, varying by 12–35%. The annual compound growth in yield remained at 1.5 to 2% for paddy, 1.5 to 2.6% for maize, 1.2 to 1.8% for wheat, and −0.2 to 1.2% for millets. In addition, there was a differential impact of rainfall and minimum temperature for all crop seasons and throughout the year. The results imply that the increasing trend of maximum temperature, in general, has benefited summer crops such as paddy and maize. As there were differences in impacts, any adaptation strategies planned and implemented should be tailor-made, considering growing seasons, altitudes, and the types of crops.